2016
DOI: 10.1002/bdm.1973
|View full text |Cite
|
Sign up to set email alerts
|

Real‐World Correlates of Performance on Heuristics and Biases Tasks in a Community Sample

Abstract: In the current study, we sought to examine whether performance on several heuristics and biases tasks and thinking dispositions was associated with real‐life correlates in a community sample of adults. We examined performance on five heuristics and biases tasks (ratio bias, belief bias in syllogistic reasoning, cognitive reflection, probabilistic and statistical reasoning, and rational temporal discounting), three thinking dispositions (actively open‐minded thinking, future orientation, and avoidance of supers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 87 publications
(122 reference statements)
3
66
1
Order By: Relevance
“…To assess the construct validity of the Verbal CRT, we measured cognitive reflection (i.e., the Numerical CRT), cognitive ability and executive functions, working memory, thinking dispositions and numeracy. Prior research found weak to medium positive correlations between these measures and the Numerical CRT (Frederick, 2005;Liberali et al, 2012;Toplak et al, 2011Toplak et al, , 2014Toplak, West, & Stanovich, 2017). We expected to find similar correlation patterns for cognitive ability, working memory, executive functioning and thinking dispositions in terms of direction even though not necessarily of the same strength due to numeracy confounding the relationships with the Numerical CRT.…”
Section: Studymentioning
confidence: 61%
“…To assess the construct validity of the Verbal CRT, we measured cognitive reflection (i.e., the Numerical CRT), cognitive ability and executive functions, working memory, thinking dispositions and numeracy. Prior research found weak to medium positive correlations between these measures and the Numerical CRT (Frederick, 2005;Liberali et al, 2012;Toplak et al, 2011Toplak et al, , 2014Toplak, West, & Stanovich, 2017). We expected to find similar correlation patterns for cognitive ability, working memory, executive functioning and thinking dispositions in terms of direction even though not necessarily of the same strength due to numeracy confounding the relationships with the Numerical CRT.…”
Section: Studymentioning
confidence: 61%
“…The ratio bias represents a clear violation of one of the most basic assumptions of rational choice-invariance across normatively equivalent problem representations. The ratio bias can even cause people to favor options with strictly worse odds (Alonso & Fernández-Berrocal, 2003;Denes-Raj & Epstein, 1994;Yamagishi, 1997; but see Lefebvre, Vieider, & Villeval, 2011), and past studies have shown the ratio bias to be associated with a number of negative traits, such as superstitious thinking (Toplak, West, & Stanovich, 2016) and low numeracy (e.g., Peters et al, 2006). Given the ubiquity of the ratio bias, several theories have been used to explain it, including cognitive-experiential self-theory (CEST; e.g., Epstein, 2013), fuzzy-trace theory (FTT; e.g., Reyna & Brainerd, 2008), anchoring and adjustment (Yamagishi, 1997), and norm theory (Miller et al, 1989).…”
mentioning
confidence: 99%
“…Beyond the importance of finding behavioural evidence for a sunk cost effect, there is a broader push for observing whether decision-making heuristics and biases matter for real-world outcomes outside the laboratory context (Arkes, 2013;Toplak et al, 2017). As previously indicated the majority of the sunk cost effect is both laboratory based and hypothetical (with some naturalistic examples).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Recent research by Toplak, West, and Stanovich, (2017) highlighted that the majority of the evidence for decision-making biases come from laboratory studies where important outcomes are not actually observed. Indeed, like the sunk cost effect, many reasoning biases necessarily mean presenting a decision-making scenario and observing whether a person makes the optimal or correct choice.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation